Urgensi pendidikan Islam di Perguruan Tinggi - Lailasari, Nadia (Maliki Interdisciplinary Journal, 2024)
Islamic education is an effort to change behavior in life. The life in question is an individual and social interaction that is always based on Islamic values. Good morals and ethics will be an indicator of the good or bad process of incorporating Islamic education that has been obtained. In the appendix of the Minister of National Education’s decision, religious education is placed in the Personality Development Subject (MPK) group. Islamic education is desired to produce human resources to strengthen faith, purity, and noble morals. Religious education wants the formation of students who provide goodness for themselves and their communities, both for personal and community interests, both from the aspects of worship and aspects of mua’amalah that students must face. Universities in Indonesia are obliged to carry out the tri dharma of higher education in carrying out their obligations so that the Indonesian people have high intelligence. The distribution of Islamic education in society must be balanced so that the quality and relevance of higher education is not in doubt, including organizing religious education or in this case Islamic education.